Steam Pipes - Howard, Mart Albert, 1855-1926 (Manuscripts, Archives, and Special Collections, Washington State University Libraries: https://libraries.wsu.edu/masc, 1898)
1 Lantern Slide: b&w; 10 x 8 cm. Steam power was employed in the Klondike to thaw gold-bearing permafrost.